Exploring application of equity-based financing through musharakah mutanaqisah in Islamic Banks in Malaysia: perspective from the industry players - Mohd Ariffin, Noraini; Kassim, Salina; Abdul Razak, Dzuljastri (International Islamic University Malaysia, 2015)
Due to the prohibition of interest in Islamic financial transactions as well as the nature of the Islamic banks which is based on the profit and loss sharing concept, the equity-based financing should be widely adopted rather than debt-based financing which is similar to that of the conventional banks. As such, financing instruments such as Muḍārabah and Mushārakah are supposedly the major financing instruments offered by the Islamic banks. However, as argued in previous studies, the Islamic banks today are concentrating more on debt-based financing, particularly Murābaḥah and Ijārah contracts. Based on survey questionnaires on sixteen Islamic banks in Malaysia, this study examines the perceptions of the Islamic bankers with regard to issues on concept, pricing and compliance to Sharīʿah of equity-based financing in Islamic banks in Malaysia. It also investigates the challenges faced by Islamic banks in adopting equity-based financing, and examines the current practice of Mushārakah Mutanāqiṣah principle that has been applied by a few Islamic banks in Malaysia. Based on the findings of this study, the respondents generally agree that the principle of profit and loss sharing element under equity-based financing represents the true spirit of Islamic banking practices. However, due to constraints arising from the complex nature of equity financing products compared to conventional debt-based products, the Islamic banks are hesitant in applying the true concept of equity financing. Several recommendations on the possible ways to gradually shift from debt-based financing to equity-based financing are suggested, particularly on the needed financial infrastructure to support adoption of the equity-based financing by the Islamic banks.